2013
DOI: 10.1103/physreve.88.042712
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical structure underlying inverse stochastic resonance and its implications

Abstract: We investigate inverse stochastic resonance (ISR), a recently reported phenomenon in which the spiking activity of a Hodgkin-Huxley model neuron subject to external noise exhibits a pronounced minimum as the noise intensity increases. We clarify the mechanism that underlies ISR and show that its most surprising features are a consequence of the dynamical structure of the model. Furthermore, we show that the ISR effect depends strongly on the procedures used to measure it. Our results are important for the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…It was often found that with close to c , spiking was terminated completely after one or a few spikes. Similar results were obtained when (a) the noise was conductance-based, as opposed to current-based, as is more appropriate for synaptic inputs, (b) current-based noise was introduced (turned-on) at a random chosen time point ), (c) channel noise was used instead of current noise (Schmerl and McDonnell 2013;Uzuntarla et al 2013), and (d) coloured noise instead of white Gaussian noise was used (Guo 2011). These variations established that the occurrence of minima in firing rate with increasing noise when is close to c is robust to significant model changes.…”
Section: Hodgkin-huxley System Of Odessupporting
confidence: 63%
See 1 more Smart Citation
“…It was often found that with close to c , spiking was terminated completely after one or a few spikes. Similar results were obtained when (a) the noise was conductance-based, as opposed to current-based, as is more appropriate for synaptic inputs, (b) current-based noise was introduced (turned-on) at a random chosen time point ), (c) channel noise was used instead of current noise (Schmerl and McDonnell 2013;Uzuntarla et al 2013), and (d) coloured noise instead of white Gaussian noise was used (Guo 2011). These variations established that the occurrence of minima in firing rate with increasing noise when is close to c is robust to significant model changes.…”
Section: Hodgkin-huxley System Of Odessupporting
confidence: 63%
“…In the case of many types of neuron (and also cardiac cells) the rhythmic behaviour is called pacemaker activity and can be driven or intrinsic. The inhibiting effect of noise on such rhythmic activity was first explored experimentally in the squid axon (Paydarfar et al 2006) and theoretically in Hodgkin-Huxley (HH) or related models of ordinary differential equations Gutkin et al 2009;Guo 2011;Tuckwell and Jost 2012;Schmerl and McDonnell 2013;Uzuntarla et al 2013) (the specific contributions of these papers are explained below) and the partial differential equation HH model (Tuckwell andJost 2010, 2011). A brief summary will be given of the results for some of the inhibitory effects of white noise in the HH systems.…”
Section: Comparison Of Reviewed Models With Stochastic Facilitationmentioning
confidence: 99%
“…During ISR, when the intensity of the (weak) noise amplitude is increased, it will first strongly inhibit the spiking activity and decrease the mean number of spikes to a minimal value, but a further increase in the noise amplitude will increase the mean number of spikes again, even above what is observed in the noise-free case. Mathematically, ISR has not been extensively studied as compared to other resonance phenomena; see [50][51][52][53], and it was recently confirmed experimentally in [54].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors considered the Morris-Lecar model neuron [17], and showed that ISR can emerge as a consequence of unreliable spike transmission [18]. In another work [19], the authors studied the phenomenon of ISR in the Hodgkin-Huxley (HH) neuron based on biophysically realistic ion channel noise. These authors also clarified the dynamical structure that underlies ISR.…”
Section: Introductionmentioning
confidence: 99%